Analisa Kerusakan Jalan Menggunakan Metode Asphalt Institute dan Penanganannya: Studi Kasus Jalan Raya Palembang-Jambi - Das, Amsori M; Setiawan, Ari; Adiguna, Muhammad Ekky Satria (Universitas Batanghari Jambi, 2024)
The Palembang-Jambi highway is one of the national roads which is important for people's lives and regional economic development. However, the road experienced significant damage due to environmental factors, construction factors and usage factors. The aim to be achieved in this research is to determine the level of damage using the institutional asphalt method and find out what treatments can be carried out. This research was conducted using primary data and secondary data. Secondary data in this research is Palembang - Jambi Highway Research Stationing data, primary data obtained during the survey is geometric data on the length and width of the road, data on the type of road damage, data on the severity of road damage. Based on the research results, the results obtained were crocodile skin cracking damage = 0.382%, sinking = 0.679%, falling = 0.0004%, holes = 0.083%, longitudinal cracks = 0.955%, peeling = 0.0508%, total damage value = 2.157%, After carrying out the analysis, the condition value obtained = 97.843%, where the level of damage is relatively low and the type of maintenance is routine maintenance.